Risk Factors for the Development of Atrial Fibrillation in the Kazakh Patients - Taizhanova, Dana; Bazarova, Nazira; Kalimbetova, Akerke; Gartung, Tatyana; Bodaubay, Roza; Muratbekova, Shynar; Rustembekkyzy, Zhansaya (Open Access Macedonian Journal of Medical Sciences, 2022)
BACKGROUND: Atrial fibrillation (AF) is the most common persistent heart rhythm disorder. AIM: Assessment of clinical predictors of atrial fibrillation in the Kazakh population. METHODS: An analytical clinical and epidemiological study of 75 patients with AF of Kazakh nationality. Descriptive analysis of medical records was carried out and the results of laboratory and instrumental research methods. Statistical analysis was carried out using the Statistica 6.0 Software package from StatSoft Inc. (USA) and MS Excel. RESULTS: In the majority of the studied patients (86.7%), atrial fibrillation was associated with hypertension, in 49.3% of patients was diagnosed with coronary artery disease. A permanent form of atrial fibrillation was observed in 63%, in 20% AF manifested itself in the form of paroxysms, in 17% AF was persistent. AF, which arose against the background of CHF, was established in 41.3% of the patients studied by us, while a decrease in LVEF below 40% was observed in 21.3% of the examined patients. In our study, diabetes mellitus was diagnosed as a comorbid pathology in 24% of patients and diabetes mellitus correlated with permanent AF in 66.7%. Thyroid pathology was observed in 9.3% cases. CRHD as a concomitant disease occurred in 12% of cases. In 5.7% of cases, AF was registered as idiopathic (primary) without a history of cardiovascular and concomitant pathology. Smoking as a risk factor was observed in 16%, alcohol consumption, was noted by 8 patients (10.7%). In 40% of cases, patients with AF were obese, 45.3% of the patients were overweight (BMI ≥25).